Advances in Prenatal Diagnosis and Genetic Research of Ciliopathies - Wei, Xingye; Wang, Tao; Zhang, Pingping; Sun, Yanmei (Journal of Contemporary Medical Practice, 2025)
Primary cilium is a kind of organelle that widely exists on the surface of various cells. It is small but complex in structure and has powerful effects. Cilia defects often lead to a series of disorders that are collectively termed “ciliopathies,” involving multiple systems. In recent years, it has been found that defects in ciliary morphology and function can lead to genetic diseases in newborns. Since cilia play a rather important role in regulating the balance of development and internal environment in vertebrates, the loss of genes related to cilia is associated with a range of diseases. Prenatal detection of renal abnormalities associated with skeletal or cerebral abnormalities should raise suspicion of multisystem ciliopathy, which is often associated with a variety of syndromes, including Meckel-Gruber syndrome, Joubert syndrome, Nephronophthisis, and Bardet-Biedl syndrome. Combined with recent studies, this article mainly summarizes four categories of cilia-related diseases in order to provide references for clinical diagnosis.